Effects of GRM4, SCN2A and SCN3B polymorphisms on antiepileptic drugs responsiveness and epilepsy susceptibility - Laith N. AL-Eitan; Islam M. Al-Dalalah; Hanan A. Aljamal (Elsevier, 2019)
Background: Pharmacotherapy of epilepsy including antiepileptic drugs (AEDs) is one of the main treatment approaches. As a biological target, sodium channels (Nav channels) and glutamate receptor genes are playing a major role in the etiology and treatment of epilepsy. Objective: This study aims to investigate the genetic associations of certain genetic polymorphisms with increased risk of epilepsy susceptibility and variability in response to AEDs treatment in a Jordanian Arab population. Method: A pharmacogenetics and case-control study on 296 unrelated epileptic Jordanian patients recruited from the pediatric neurology clinic at the Queen Rania Al-Abdullah Hospital (QRAH) in Amman, Jordan and 299 healthy individuals was conducted. Children up to 15 years old which receiving AEDs for at least three months were scanned for genetic association of 7 single nucleotide polymorphisms (SNPs) within three candidate genes (SCN2A, SCN3B and GRM4) with epilepsy susceptibility. Results: SCN2A rs2304016 (P = 0.04) and GRM4 rs2499697 (P = 0.031) were statistically significant with generalized epilepsy. Haplotype of CAACG GRM4 was genetically associated with epilepsy and partial epilepsy (P = 0.036; P = 0.024, respectively). This study also found that TGTAA genetic haplotype formed within GRM4 gene was associated with generalized epilepsy susceptibility (P = 0.006). While, no significant linkage of SCN3B rs3851100 to either disease susceptibility or drug responsiveness was found. Conclusion: This study identified no significant associations of allelic or genotypic SNPs with the susceptibility of epilepsy and medication response with an exception of rs2304016 and rs2499697 SNPs that were associated with the generalized type of epilepsy among Jordanian population. Further studies are required in different populations to confirm our results and identify genetic factors that involved in susceptibility and treatment response. Keywords: Epilepsy, Pharmacogenetics, Anticonvulsants, Sodium channels, Glutamate receptors, Jordan